PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PADA PT. MANDIRI CASH AND CREDIT CABANG BANDAR LAMPUNG - Suwandi Suwandi (Universitas Catur Insan Cendekia (CIC) Cirebon, 2017)
Abstract To create a high performance, it requires an optimal work enhancement and able to empower the potential Human Resources owned by employees in order to create organizational goals, so that will contribute positively to the development of the organization. In addition, the organization needs to pay attention to various factors that can affect employee motivation, in this case it is necessary for the role of organization in order to increase employee motivation and create a conducive working environment, to encourage the creation of professional attitudes and actions, in completing the work in accordance with the duties and responsibilities answer each. The research will be conducted is a type of Descriptive Research, this type of research is research that intends to make exposure in a systematic, factual, and accurate about the facts and properties of a particular population. This study used 92 respondents research. There are 3 (three) variables in this research, that is 2 (two) independent variables (X1 and X2) and 1 (one) dependent variable. Where work motivation (X1) and work environment (X2) as independent variable, and employee performance (Y) as dependent variable. From the results of data processing has been successfully found the answer hypothesis, namely as follows: there is influence between work motivation (X1) on employee performance (Y), with the level of influence (R-square) of 28.9% which means work motivation gives the effect of 28 , 9% on employee performance. There is influence between work environment (X2) and employee performance (Y), with influence level 28,3% which mean that work environment give influence 28,3% to employee performance. There is influence between work motivation (X1), work environment (X2) on employee performance (Y), with influence level of 29,6% which mean that work motivation and work environment give influence simultaneously equal to 29,6% to employee performance. Keywords: Work Motivation, Work Environment, Performance